Measurements on Five Characterizing Properties of Graphene Oxide and Reduced Graphene Oxide Foils. Issue 6 (21st January 2022) - Torrisi, Lorenzo; Cutroneo, Mariapompea; Torrisi, Alfio; Silipigni, Letteria
Abstract : Micrometric foils of graphene oxide are prepared in the laboratory starting from water dispersed solution of graphene oxide at low concentration. Measurements on five physical properties have been performed in the foils of graphene oxide and reduced graphene oxide. The reduction is obtained thermally, using IR and UV laser irradiations and MeV helium ion beam irradiations at different fluence. The parameters such as the atomic composition, the mass density, the surface roughness, the wetting ability, and the electrical conductivity are investigated. This last parameter assumes different values for the pristine graphene oxide foils and for the reduced ones. Comparison of experimental measurements with the literature data and the results and discussion are presented. Abstract : The reduction of graphene oxide (GO) can be obtained using different techniques, such as thermal annealing, laser beam, and ionizing irradiations. Five important properties can modified by the GO reduction, such as the C/O atomic ratio, the mass density, the wetting ability, the surface roughness and the electrical conductibility, which increase depending on the level of obtained reduction.